BUDIDAYA JAMUR PERUSAK KAYU III. BUDIDAYA AURICULARIA POLYTRICA PADA DOLOK LIMA JENIS KAYU - Sihati Suprapti (Jurnal Penelitian Hasil Hutan, 1988)
Ear mushroom  (Auricularia polytrica) was cultivated  on logs of five  wood species, i.e. hamerang (Ficus grossularoides Burn.f.), jeungjing (Albizia  falcataria (L.) Fosb.), jirak  (Symplocos fasciculata Zoll.),  kihuut  (Vernonia arborea  Ham.)  and manii  (Maesopsis eminii Engl.). The  logs were  kept  slanted  on an angle of ± 60°  with  bamboo  supports  in a 1.5 m by 2 m room  roofed  with  bamboo plait,  at Bogor.  The mature  mushroom was harvested  daily after  the growth  of the fruiting  body.The  logs start  producing   fungus  two  months after  inoculation. The  highest  harvest  was obtained  at  fourth   month of  observation. The  average yield  per month  per  m3  of  log was obtained  from  kihuut (15.69  kg), jeungjing  (10.76 kg), manii  (9,46  kg),  hamerang  (8.59   kg) and jirak  (1.29 kg).After  seven  month   observation, an  average yield  of  1.05 kg log (kihuut), 0. 725 kg  (jeungjing), 0.556  kg  (manii), 0.349 kg  (hamerang],  and  0.125 kg (jirak)  were  obtained.   Relative   high  total  yield   of ear mushroom   during  the seven month   observation   was obtained  from  kihuut   (109.84 kg),  jeungjing  (75.285  kg),  manii  (66.202 kg),  hamerang (60.103 kg) and  the  lowest  total yield  was on jirak  (9.036 kg) per  m3  of  log.